ENVIRONMENTAL FACTORS: DOMINANT MOTIVATION OF THE BONGAN COMMUNITY TO SUPPORT THE DEVELOPMENT OF TOURIST VILLAGE - Oka, I Made Darma; Darmayanti, Putu Widya (Institut Pariwisata dan Bisnis Internasional, 2020)
This article discusses the factors that motivate the Bongan’s community to support the development of tourist village. The research used qualitative and quantitative data collected by distributing questionnaires to and conducting an in-depth interview with those who are knowledgeable of the tourism development at the Bongan village. The samples included 100 respondents determined using the proportional random sampling technique. The data were analyzed using the confirmatory factor analysis technique to confirm the factors that motivate the local community to support the development of tourist village. The research shows that the environmental, social, community participation, and cultural factors have significantly contributed to support the development of tourist village. The environmental factor is the most dominant one followed by the social, community participation, and cultural factors. This mean that the environmental factor is the main reason why the local community supports the development of tourist village at the Bongan village.